Деякі відмінності діагностики і лікування грампозитивного та грамнегативного сепсису - Шаповал, Сергій Дмитрович; Shapoval, S. D. (My University, 2024)
Мета дослідження. З’ясувати відмінності клініко-лабораторних ознак грампозитивного та грамнегативного сепсису та особливості їх перебігу. Матеріали і методи. Проведено дослідження 317 хворих із сепсисом, які перебували на обстеженні та лікуванні у міському гнійно-септичному центрі м. Запоріжжя за період 1991-2024 р. У всіх випадках спостерігався позалікарняний сепсис, тобто сепсис, який розвинувся протягом 48 годин перебування пацієнта в стаціонарі. Сформовані дві основні групи: 1 – хворі з грам (+) сепсисом (168 пацієнтів – 53 %), 2 – з грам (-) сепсисом (149 – 47 % хворих). Крім цього, в середині кожної групи, сформовані дві підгрупи: ті, що лікувалися протягом 1991-2016 рр. ( І підгрупа) – 235 хворих, ІІ – протягом 2017-2024 р. — 82 пацієнтів. Серед сепсису неускладнена форма захворювання відмічена у 208 хворих – (65,6%), а септичний шок (СШ) – 109 пацієнтів (34,4%). The course of gram-positive and gram-negative sepsis has significant differences that should be taken into account when conducting complex treatment. Mortality in such patients remains very high, and hospital stay requires significant material costs. The aim of the study. To find out the differences between clinical and laboratory signs of gram-positive and gram-negative sepsis and the features of their course. Materials and methods. A study was conducted of 317 patients with sepsis who were examined and treated in the city purulent-septic centre of Zaporizhzhia in the period 1991- 2024. In all cases, community-acquired sepsis was observed, i.e. sepsis that developed within 48 hours of the patient’s hospital stay. Two main groups were formed: 1 — patients with gram(+) sepsis (168 patients — 53%), 2 — patients with gram(-) sepsis (149 patients — 47%). In addition, within each group, two subgroups were formed: those treated in 1991-2016 (subgroup I) — 235 patients, and subgroup II — in 2017-2024 — 82 patients. Among sepsis, the uncomplicated form of the disease was noted in 208 patients (65.6 %), and septic shock (SS) — 109 patients (34.4 %).
Some differences in the diagnosis and treatment of gram-positive and gram-negative sepsis
Keywords: грам(+) та грам(-) сепсис; перебіг; діагностика; лікування; летальність; gram(+) and gram(-) sepsis; course; diagnosis; treatment; mortality